MANAJEMEN PENDIDIKAN INKLUSI DI SEKOLAH DASAR SUMBERSARI 1 KOTA MALANG - Agustin, Ina (JURNAL PENDIDIKAN DAN PENGEMBANGAN MANUSIA, 2016)
Implementation of inclusive education is a system that requires special education services for all children with special needs to get education in the same classes alongside regular students. This study aims to determine the implementation of inclusive education management and the obstacles encountered in the implementation of inclusive education management in SDN Sumbersari 1 Malang. This study used descriptive qualitative method. In collecting data, the researcher used data collection techniques include: observation, interviews and documentation. The Subjects of research were principals, homeroom, a special guidance counselor and parents. The results of this study show that: 1) The implementation of inclusive education management can be seen from the number of students with special needs in 2015/2016 academic period are 19 people, has 2 (two) special supervising teachers, and the curriculum has been modified according to the needs of students, 3) The obstacle encountered in the study was the funding of education, and some inadequate facilities and infrastructure as well as the lack of teacher assistant.